2015
DOI: 10.1007/s11771-015-2812-3
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet basis construction method based on separation blast vibration signal

Abstract: As wavelet basis in wavelet analysis is neither arbitrary nor unique, the same signal dealing with different wavelet bases will generate different results. Therefore, how to construct a wavelet basis suitable for the characteristics of the analyzed signal and solve its algorithm and realization is a fundamental problem which perplexed many researchers. To solve these problems, in accordance with the basic features of the measured millisecond blast vibration signal, a new wavelet basis construction method based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The empirical results have demonstrated that the sym7, sym8 [24], db6 [25], and db8 [26] wavelet basic functions are particularly effective in handling blast vibration signals The 'ddencmp' function in MATLAB provides default values for denoising or compression for the critically sampled discrete WD or WPD. The default threshold estimation methods encompass 'rigrsure', 'heursure', 'sqtwolog', 'minimaxi'.…”
Section: Noise Reductionmentioning
confidence: 99%
“…The empirical results have demonstrated that the sym7, sym8 [24], db6 [25], and db8 [26] wavelet basic functions are particularly effective in handling blast vibration signals The 'ddencmp' function in MATLAB provides default values for denoising or compression for the critically sampled discrete WD or WPD. The default threshold estimation methods encompass 'rigrsure', 'heursure', 'sqtwolog', 'minimaxi'.…”
Section: Noise Reductionmentioning
confidence: 99%
“…The ability of WT to decompose and reconstruct signals through Wavelet functions enables the extraction of signal features at different scales, making it particularly effective for the identification of transient impulses [16]. Researchers have highlighted the importance of using appropriate wavelet bases in wavelet analysis, as different bases can lead to varying results when analyzing the same signal [17]. Studies have shown that wavelet analysis is highly suitable for detecting and analyzing transient disturbances, outperforming various other detection algorithms [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have also proposed improved methods related to EMD and WT to adapt to the complexity of signal and the diversity of applications, such as ensemble empirical mode decomposition (EEMD) [21] and variational mode decomposition (VMD) [16,22]. There are many ways to improve wavelet denoising methods, such as improving the threshold function to solve the problem that reconstruction signal may oscillate or distort that caused by traditional threshold functions [23][24][25][26][27][28][29][30][31], setting adaptive threshold [32,33], finding the optimal wavelet basis [34][35][36], and setting self-adaptive wavelet decomposition level [15]; some scholars combine EMD and WT [37].…”
Section: Introductionmentioning
confidence: 99%